The Effect of Mind Mapping Methods Types of Mind Map Syllabus on Mathematics Problem Solving Ability in Flat Side Space Construction Materials of Class VIII Students of SMP Negeri 1 Karangreja District Purbalingga - Ika Purwati; Debby Amaliah Putri (International Journal of Research in Mathematics Education, 2023)
Abstract: This study aims to determine whether there is an influence of the syllabus mind mapping method on the mathematical problem solving abilities of class VIII students of SMP Negeri 1 Karangreja, Purbalingga Regency. Mathematical problem solving ability is a quality possessed by someone to solve mathematical problems so that the goals to be achieved are resolved properly. One of the factors that influence the ability to solve mathematical problems is the model or method used in learning. The researcher chose to use the mind mapping method, a type of syllabus mind map, to improve students' mathematical problem solving abilities. This study used quantitative research (experimental) with a Quasi-Experimental Design. The population of this study were all class VIII which totaled 5 classes. The samples of this study were class VIII A, which consisted of 26 students and class VIII B, which consisted of 22 students. Collecting data in this study used a test consisting of a pretest and posttest. Data analysis used the t test and the N-Gain test using the SPSS version 25 application. The results of this study indicate that there is an influence of the syllabus type mind mapping method on the math problem solving abilities of class VIII students of SMP Negeri 1 Karangreja, Purbalingga Regency. The N-Gain results show that the N-Gain of the experimental class is included in the high category with an average N-Gain of 0.70 and the control class is included in the medium category with an average N-Gain of 0.54. So that the increase in students' mathematical problem solving abilities in the experimental class is higher than the control class. Keywords: Mind Mapping , Problem Solving